2004
DOI: 10.1183/09031936.04.00030404
|View full text |Cite
|
Sign up to set email alerts
|

Value of imprint cytology for ultrasound-guided transthoracic core biopsy

Abstract: The aim of this study was to investigate the possible additional diagnostic information provided by imprint cytology when performing ultrasound-guided transthoracic core biopsy and to evaluate whether it could optimise the biopsy procedure.A total of 155 transthoracic core biopsies with touch imprint smears were performed under ultrasound guidance, with 127 malignant and 28 benign lesions. The imprint smears were stained using Riu9s method and interpreted by a cytopathologist. These were compared with the hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…These values are comparable to some of the studies in the literature and are even better than some (table 5) [6,7,8,9,10,11,12,13,14,15,16]. It should be pointed out here that biopsy diagnosis is attained after immunohistochemistry which was not possible on cytology.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…These values are comparable to some of the studies in the literature and are even better than some (table 5) [6,7,8,9,10,11,12,13,14,15,16]. It should be pointed out here that biopsy diagnosis is attained after immunohistochemistry which was not possible on cytology.…”
Section: Discussionsupporting
confidence: 70%
“…Our data clearly show that the results of ROSAC obtained by the cytotechnologist are equivalent to or better than most of the studies in the literature [9,10,12,13], besides being very cost-effective.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Recently, PAULOSE et al [13] showed that imprint cytology could assist rapid diagnosis of lung cancer metastasis in mediastinal lymph nodes following CT-guided TNB. LIAO et al [14] demonstrated improved diagnostic accuracy by using imprint cytology following ultrasound (US)-guided TNB of peripheral lung lesions. The role of touch imprint cytology in CT-guided coaxial core biopsy of intrathoracic lesions has not been investigated.…”
mentioning
confidence: 99%
“…Touch imprint cytology (TIC) offers sensitivity and specifi city that is equivalent to that of frozen sections. TIC preserves the original sample for permanent fi xation and avoids potential sample loss, which is virtually impossible with frozen sectioning (Creager et al 2002, Khana et al 1988, Hahn et al 1995, Liao et al 2004, Suen et al 1976, Brogi et al 2005.…”
mentioning
confidence: 99%